GOVERNANCE, ECONOMICS, AND IDENTITY: A CASE STUDY OF BENISHANGUL GUMUZ (1991-2018) - Lionel , Bender (International Journal of Political Science and International Relations (IJPSIR), 2022)
The Mätäkäl Region in Western Ethiopia is a significant geographical area characterized by diverse topography and agro-ecological zones. This study aims to provide an extensive analysis of the region's landscape, climate, and agricultural potential. The Mätäkäl Zone, located in the northwestern part of Ethiopia, shares its borders with the Republic of Sudan to the north of the Blue Nile, Gondar to the north, Wälläga and Asossa to the south, and the former province of Gojjam to the east. The region's topography consists of 74% flat plains, 16% hilly and plateaus, 6% valleys, and 4% mountainous areas. Moreover, it is divided into three major climatic zones: qolla, covering approximately 75% of the region, Woina Däga accounting for 24%, and Däga encompassing only. This research examines the temperatures and rainfall patterns in the Mätäkäl Zone. During the rainy season, daily temperatures range from 20°C to 25°C, while in the dry season, they soar to 35°C to 40°C. The region experiences annual rainfall variations from 800 to 2000mm, with the hottest period occurring from February to April. Minimum daily temperatures range from 12°C to 20°C, depending on the season and altitude. Understanding the climatic conditions and their variations is crucial for devising appropriate agricultural strategies and food security measures in the region. The study combines data from various governmental reports, including the Mätäkäl Zonal Agricultural Department and the Beniŝangul-Gumuz Region Food Security Strategy. By analyzing and synthesizing this information, the research sheds light on the potential challenges and opportunities for sustainable agriculture in the Mätäkäl Region. Furthermore, it explores the implications of climate change and its possible effects on the region's agricultural productivity and food security.